Studi Pemikiran Dakwah KH. X tentang Gerakan Dakwah Tarbiyah - Fitria Nur Hasannah; Wildan Yahya (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. KH. X is a da'wah figure who is very well known by the Tarbiyah movement. The alignment of his personal da'wah with the Tarbiyah movement influenced the development of Tarbiyah da'wah in Indonesia. The preaching thought of KH. X was a good change for the Tarbiyah movement. This research is a research on the study of the da'wah thought of KH. X about the Tarbiyah da'wah movement. The purpose of this study was to determine the thought of da'wah by looking at the material, methods and media of da'wah KH. X and the Tarbiyah Da'wah Movement KH. Rahmat Abdullah. This research uses descriptive qualitative method. The type of research is library research with content analysis techniques on research data sources. The results of this study include four discussions. First, the material for preaching KH. X which is divided into three problems, namely the problem of aqidah, shari'ah and morals contained in the books